Why Do Academics Use Academic Social Networking Sites? - Meishar-Tal, Hagit; Pieterse, Efrat (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
Academic social-networking sites (ASNS) such as Academia.edu and ResearchGate are becoming very popular among academics. These sites allow uploading academic articles, abstracts, and links to published articles; track demand for published articles, and engage in professional interaction. This study investigates the nature of the use and the perceived utility of the sites for academics. The study employs the Uses and Gratifications theory to analyze the use of ASNS. A questionnaire was sent to all faculty members at three academic institutions. The findings indicate that researchers use ASNS mainly for consumption of information, slightly less for sharing of information, and very scantily for interaction with others. As for the gratifications that motivate users to visit ASNS, four main ones were found: self-promotion and ego-bolstering, acquisition of professional knowledge, belonging to a peer community, and interaction with peers.